Pre-operative anxiety in patients undergoing coronary artery bypass graft surgery â A cross-sectional study - C. Ramesh; Baby S. Nayak; Vasudev Baburaya Pai; Anice George; Linu Sara George; Elsa Sanatombi Devi (Elsevier, 2017)
Background: Coronary artery bypass graft surgery is an important treatment for the patients with coronary artery disease to reduce angina and enhance the quality of life. Anxiety is a usual reaction to a stressful situation and is existing in patients awaiting surgery. Objective: The objective of the study was to assess pre-operative anxiety in patients who were undergoing coronary artery bypass graft surgery. Methods: A cross-sectional study consisting of 140 patients undergoing coronary artery bypass graft surgery were included in the study using a convenience sampling technique in a tertiary care referral hospital. The data was collected using state-trait anxiety inventory. The data were entered into SPSS (version â 20.0) for windows and descriptive and inferential statistics were performed. Results: The study enrolled 140 (117 males and 23 females) patients. Their mean age was 57.29Â Â±Â 8.14 (range 35â70Â years). Most of the patients 118 (84%) had preoperative anxiety before coronary artery bypass graft surgery. There was an association found between gender and anxiety with Pearson chi-square value of 11.57 (pÂ <Â 0.001). Discussion: Patients undergoing coronary artery bypass graft surgery is experiencing the high level of pre-operative anxiety and females had higher anxiety than the males. Identification of the pre-operative anxiety in patients undergoing CABG surgery is essential because it helps the health professionals and nurses to develop effective and appropriate interventions. Keywords: Preoperative period, Anxiety, Coronary artery bypass, Perioperative care